Hak Konstitusional Partai Politik dan Konsekuensi Calon Presiden-Wakil Presiden Tunggal di Indonesia - Abdul Ghoffar (Fakultas Hukum Universitas Islam Indonesia, 2018)
This study aimed to examine the constitutional rights of political parties in nominating President-Vice President candidates, and the possibility of single candidate to result in a vacancy in the position of President-Vice President in Indonesia. This study used normative legal method, with a statute approach, historical approach, and a comparative approach. The results of this study concluded that: First, in terms of constitution, there is no presidential threshold on political parties to propose President-Vice President candidates. In addition, according to Article 6A paragraph (2) of the 1945 Constitution of the Republic of Indonesia, all political parties that qualify as the participants in the 2019 Election have the right to nominate President-Vice President candidates; not only those parties that have representatives in the House of People’s Representatives (DPR). Second, a single candidate has the potential to result in a vacancy in presidency because if the winner is an empty box, then it is certain that Indonesia does not have a President-Vice President